2015
DOI: 10.15172/pneu.2015.6/488
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infection and bacteraemia as causes of non-malarial febrile illness in African children: a narrative review

Abstract: The replacement of “presumptive treatment for malaria” by “test before treat” strategies for the management of febrile illness is raising awareness of the importance of knowing more about the causes of illness in children who are suspected to have malaria but return a negative parasitological test. The most common cause of non-malarial febrile illness (NMFI) in African children is respiratory tract infection. Whilst the bacterial causes of NMFI are well known, the increasing use of sensitive techniques such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
1
9
1
Order By: Relevance
“…Furthermore, one of the two fatalities that occurred in our study was caused by respiratory failure. Lower respiratory tract infections (LRTI) were the main cause of febrile illness in children, as found in similar studies 14 . These results stress the need for fast and correct malaria diagnosis and radiology in resource-limited areas.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, one of the two fatalities that occurred in our study was caused by respiratory failure. Lower respiratory tract infections (LRTI) were the main cause of febrile illness in children, as found in similar studies 14 . These results stress the need for fast and correct malaria diagnosis and radiology in resource-limited areas.…”
Section: Discussionmentioning
confidence: 53%
“…Studies in children in sub-Saharan Africa have similarly found RTIs to be the most common cause of acute febrile illness. 10,[12][13][14]24 However, our results also suggest that some of the clinical diagnoses made by the health workers in patients with NMFIs were likely inaccurate. Sepsis was diagnosed in almost one-third of cases; however, etiological studies in adults or children in similar settings have shown that only a very small proportion of outpatient fevers, ranging from 1.3% to 4.2%, are caused by bloodstream infections.…”
Section: Discussionmentioning
confidence: 61%
“…14,15 In such occasions, the epidemiological landscape becomes even more complicated, requiring accurate diagnosis of the RTI-causative pathogen for proper management of patients with comorbidities. 16 In this context, nucleic acid amplification testing (NAAT) 17-19 is a promising candidate to overcome the aforementioned challenges and offer high sensitivity and specific pathogen identification that can contribute to a reliable downstream patient management. Especially when conducted on an automated platform, NAAT offers the potential for shifting the diagnosis to the patient side.…”
Section: Introductionmentioning
confidence: 99%